Tracheal Transplantation - Delaere, Pierre (Leuven University Press, 2026)
Defining the requirements for a successful transplantation of tracheal segments The trachea is one of the most fascinating organs in the human body. At first sight, it may appear to be a simple tube for air transport to and from the lungs. However, the cartilaginous framework of this airway, combined with its ultrathin mucosal lining and rich, but difficult to handle, blood supply, makes it to one of the most challenging tuberous organs to repair and transplant. In 2011, the trachea was heralded as the first organ that could be engineered with stem cells. In the last years however, it became clear that this achievement was based on scientific deception. Richly illustrated and in full colour, this ebook is intended to highlight both the intricacies of the laryngotracheal airway and the reconstructive approaches that can potentially restore airway function, particularly in relation to laryngotracheal stenoses and defects. Although, allotransplantation to restore segmental defects is still an unmet need, Tracheal Transplantation. Current possibilities attempts to define the requirements needed for a successful transplantation of tracheal segments. Includes video clips * Due to the nature of the video clips, a YouTube account might be required in order to enable access. Contributors (all KU Leuven): Herbert Decaluwé (Thoracic Surgery), Paul De Leyn (Thoracic Surgery), Margot Den Hondt (Plastic & Reconstructive Surgery), Christophe Dooms (Pulmonology), Jeroen Meulemans (ORL Head & Neck Surgery), Thomas Nevens (Plastic & Reconstructive Surgery), Katarina Segers (Plastic & Reconstructive Surgery), Vincent Vander Poorten (ORL Head & Neck Surgery), Dirk Van Raemdonck (Thoracic Surgery), Geert Verleden (Pulmonology), Robin Vos (Pulmonology), Jan Vranckx (Plastic & Reconstructive Surgery), Jonas Yserbyt (Pulmonology)